Constitutional adjudication in Ethiopia: Exploring the experience of the House of Federation (HoF) - Fiseha, A (Mizan law review, 2010)
Ethiopia has adopted a federal system de facto since 1991, and de jure since 1995 with a view to decentralizing power and resources from the center and to accommodate the diverse ethno-linguistic groups that exist in the country. As constitutionally entrenched division of power between federal and state governments is at the bedrock federalism and as the division of powers often is far from clear, it is inherent in any federal system that there must be an organ for the adjudication of constitutional issues and for the settlement of disputes concerning the competence of the two levels of governments. In the 1995 Ethiopian federal constitution, this task is entrusted to the nonlegislative second chamber, otherwise known as the House of Federation (HoF). This article attempts to review the experience of the HoF ever since its establishment by assessing the relevant Ethiopian laws and the decisions of the HoF. With this in view the first sections are devoted, though briefly, to the discussion of the varied practices adopted in some constitutional systems. The remaining sections discuss the underlying reasons for the adoption in the 1995 federal Constitution of Ethiopia, the HoF as a unique institution for the adjudication of disputes and explore its jurisdiction vis-à-vis the judiciary and analyse its achievements and challenges. The general trend observed is that despite institutional and pragmatic challenges, the HoF has over the years evolved as a legitimate body for the settlement of disputes at least as far as issues of high political and constitutional significance are concerned. This article further discusses the extent to which the role of the judiciary has been affected owing to the role of the HoF.